An integral equation associated with P+2Fp+1 - Saxena, R.; Kalla, S. (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
The solutión of an integral equation associated with a generalized hypergeometric polynomial p+2Fp+1 is obtained in terms of certain integral operators by the application of Rodrigues formula. The result given recently by Dixit (1978) is derived as a special case